Improving The Creative Economy Through Training in Making Aloe Vera Dish Liquid Soap with Participatory Rural Appraisal Method - Desak Made Darmawati; Luthpi Safahi; Ervin Azhar; Muhammad Alimudin; Nur Busyra (TAAWUN, 2025)
This community service program is carried out to improve skills for the women of the Bekasi Ta'lim Bakormata Council as a training program for making liquid dish soap to enhance the community's creative economy in increasing family needs. This method of service uses Participatory Rural Appraisal. The training participants of the partner group amounted to 50 people. The implementation is carried out in stages, with lecture methods, direct practice, and mentoring, which takes 3 months. The results of this program showed a significant increase in the enthusiasm of participants in the training by 45% succeeded in showing excellent results, the activity was carried out in groups, then it could be used as a home business, as evidenced by the sales of 500 bottles, with a unit price of Rp.10,000, per bottle. This training has also succeeded in encouraging local economic diversification, improving welfare, and strengthening the creative economy's potential at the Ta'lim Bakormata Assembly. This program can be a model adopted by other assemblies in the surrounding community.